2017
DOI: 10.1021/acsami.7b09915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-fullerene Acceptors’ Side Chains on the Morphology and Photovoltaic Performance of Organic Solar Cells

Abstract: Three indacenodithieno[3,2-b]thiophene (IT) cored small molecular acceptors (ITIC-SC6, ITIC-SC8, and ITIC-SC2C6) were synthesized, and the influence of side chains on their performances in solar cells was systematically probed. Our investigations have demonstrated the variation of side chains greatly affects the charge dissociation, charge mobility, and morphology of the donor:acceptor blend films. ITIC-SC2C6 with four branched side chains showed improved solubility, which can ensure the polymer donor to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…For example, after changing the phenyl side chains of ITIC with thienyl side chains, the molecule ITIC‐Th displays enhanced intermolecular interaction and higher electron mobility . It should be noted that most of SMAs have symmetrical side chains, which sometimes strongly influence the molecular crystallinity and molecular packing properties . Bo and co‐workers adopted a creative approach to design acceptors with asymmetrical side chains, which can effectively modulate the absorption, energy levels, and packing properties of the corresponding materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, after changing the phenyl side chains of ITIC with thienyl side chains, the molecule ITIC‐Th displays enhanced intermolecular interaction and higher electron mobility . It should be noted that most of SMAs have symmetrical side chains, which sometimes strongly influence the molecular crystallinity and molecular packing properties . Bo and co‐workers adopted a creative approach to design acceptors with asymmetrical side chains, which can effectively modulate the absorption, energy levels, and packing properties of the corresponding materials.…”
Section: Introductionmentioning
confidence: 99%
“…[30] It should be noted that most of SMAs have symmetrical side chains, which sometimes strongly influ ence the molecular crystallinity and molecular packing prop erties. [31,32] Bo and coworkers adopted a creative approach to design acceptors with asymmetrical side chains, which can effectively modulate the absorption, energy levels, and packing properties of the corresponding materials. As a result, better performance could be achieved for the asymmetrical side chains containing materials compared to their symmetrical counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] Currently, there are three main modifications to the chemical structures of the A-D-A type nonfullerene acceptors, including using different side chains, changing structures of end A units, and replacing the central D units. [35][36][37][38][39][40][41] Particularly, there are great interests in expanding the chemical structures of the D cores, and fluorene, spiro-fluorene, carbazole, heptacyclic benzodi(cyclopentadithiophene) (FBDT), dithieno[3,2-b]pyrrolobenzotriazole (BZTP), dithienonaphthalene (DTN), indenoindene, naphtho[1,2-b:5,6-b']dithiophene (NDT), and carbon-oxygen-bridged ladder-type unit (COi8) have been investigated in recent years. [42][43][44][45][46][47][48][49][50][51][52][53] It was found that introducing these new D units in the nonfullerene acceptors could result in tunable energy levels and band gaps, electron transports, and bulk-heterojunction (BHJ) morphology.…”
Section: Introductionmentioning
confidence: 99%
“…BT units were inserted as the bridge linkers (A2) and rhodanine groups were attached as terminal units (A1), respectively, which was similar to the terpolymer strategy in polymeric donor systems . The alkyl chains with different length were grafted from the rhodanine skeleton to finely tune the solubility of the target molecules . These two NFAs exhibited quite different packing behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Most successful NFAs reported up to date, such as 3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone)-5,5,11,11-tetrakis(4hexylphenyl)-dithieno[2,3-d:2′,3′-d′]-s-indaceno [1,2-b:5, 6-b′]-dithiophene, [6] 3,9-bis(2-methylene-(5&6-methyl-(3-(1,1dicyanomethylene)-indanone)-5,5,11,11-tetrakis(4-hexylphenyl) dithieno[2,3-d:2',3'-d′]-s-indaceno [1,2-b:5,6-b′]-dithiophene, [7] www.advancedsciencenews.com www.small-methods.com length were grafted from the rhodanine skeleton to finely tune the solubility of the target molecules. [27] These two NFAs exhibited quite different packing behaviors. TIDT-BT-R2 with shorter alkyl chain showed enhanced photo-induced charge separation, better charge transport and collection properties.…”
Section: Introductionmentioning
confidence: 99%